Broadway Musicals and the Christian Sermon: Communicating Moral Reasoning, Church Values, and Prosocial Behaviors - Lukenbill, W. Bernard (Journal of religious and theological information, 2017)
This article considers the influence of Broadway musicals on the spiritual growth, prosocial attitudes, church values, and moral reasoning of adults when used in Christian congregational worship. Can a church structure and use Broadway musicals in sermons to encourage its lay congregation to identify moral reasoning and recognize core church values and prosocial ideas through sermons based on Broadway musical theater? We applied humanistic psychologist Lawrence Kohlberg's theory of moral reasoning and development considered along with the church's stated core values and prosocial behavior to test if these themes were reflected in the rhetoric of sermons based on Broadway musicals presented from 2008-2015. Findings indicate that this series was well received by the congregation and leadership. Suggestions for further research and church applications for Christian education are given. This research highlights the importance of church archives and library support for the further development of information about the church and its role in society.